Engaging Millennials: Role of Quality of Work Life, Psychological Safety, Psychological Capital, and Inclusive Leadership (A Study of 3-5 star Hotel Employees in Yogyakarta City) - Singarimbun, Abigael Sribuena; Suharti, Lieli (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The millennial generation dominates the workforce in Indonesia, earning the title of "fleas" or the "hopping generation" due to the high intensity of job changes. The purpose of this study is to develop an integrative model for engaging millennials in the workplace that incorporates individual resources (psychological capital), and resources derived from the workplace (inclusive leadership, quality of work life, and psychological safety).Methodology: This study used a quantitative approach. The research sample comprises 152 hospitality employees working in 3-5-star hotels in Yogyakarta city. The data was collected using a purposive sampling technique. A questionnaire was distributed to the research sample and was then analyzed using the PLS-SEM technique.Finding: Inclusive leadership and psychological capital exert a positive and significant effect on the quality of work life. The quality of work life also has a positive and significant effect on work engagement; and it acts as a mediator between inclusive leadership and work engagement, as well as between psychological capital and work engagement. However, psychological safety does not enhance the effect of inclusive leadership on the quality of life or the effect of psychological capital on work engagement. Therefore, organizations must strive to fulfill the employees' quality of work life to maximize the psychological capital and the application of inclusive leadership within the organization, thereby fostering work engagement in the workplace.Conclusion: The results of this study indicate that the quality of work life plays a pivotal role in work engagement and inclusive leadership has a positive impact on the quality of life among the millennial generation employee.